PENGARUH PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF DAN BERPIKIR KRITIS MATERI SPLDV SISWA SMP - Ahya Anfaza Rahadian; ahmad ahmad (Prima: Jurnal Pendidikan Matematika, 2026)
This study was conducted to examine the impact of the Project Based Learning (PjBL) model on junior high school students’ creative and critical thinking skills in learning Systems of Linear Equations in Two Variables (SLETV). A quantitative approach was employed through a quasi-experimental design, specifically the Posttest-Only Control Group Design. The research population comprised all eighth-grade students of SMP Negeri 2 Purbalingga. Two classes were selected as research samples, with one serving as the experimental group that received instruction through the PjBL model and the other functioning as the control group that experienced conventional teaching practices. Data were obtained using a structured objective test accompanied by reasoning-based items. The collected data were analyzed through descriptive statistical techniques, normality and homogeneity testing, Independent Samples t-test, and Multivariate Analysis of Variance (MANOVA). The findings revealed that students in the experimental group achieved a higher mean posttest score (83.83) than those in the control group (70.17). Statistical analysis indicated a significance value of 0.000, which was lower than the 0.05 threshold, demonstrating that the implementation of PjBL significantly improved students’ creative and critical thinking skills when examined separately. In addition, the MANOVA results produced the same significance value, confirming that the learning model simultaneously affected both cognitive abilities. These findings suggest that learning activities involving project development, investigation, and authentic problem-solving situations can foster students’ ability to generate ideas creatively, evaluate information critically, and construct solutions more effectively than conventional instructional approaches.